In vivo phenotyping of the microvasculature in necrotizing enterocolitis with multicontrast optical imaging. (1st June 2022) - Senarathna, Janaka; Kovler, Mark; Prasad, Ayush; Bhargava, Akanksha; Thakor, Nitish V.; Sodhi, Chhinder P.; Hackam, David J.; Pathak, Arvind P.
Abstract: Objective: Necrotizing enterocolitis (NEC) is the most prevalent gastrointestinal emergency in premature infants and is characterized by a dysfunctional gut microcirculation. Therefore, there is a dire need for in vivo methods to characterize NEC‐induced changes in the structure and function of the gut microcirculation, that is, its vascular phenotype. Since in vivo gut imaging methods are often slow and employ a single‐contrast mechanism, we developed a rapid multicontrast imaging technique and a novel analyses pipeline for phenotyping the gut microcirculation. Methods: Using an experimental NEC model, we acquired in vivo images of the gut microvasculature and blood flow over a 5000 × 7000 μm 2 field of view at 5 μm resolution via the following two endogenous contrast mechanisms: intrinsic optical signals and laser speckles. Next, we transformed intestinal images into rectilinear "flat maps, " and delineated 1A/V gut microvessels and their perfusion territories as "intestinal vascular units" (IVUs). Employing IVUs, we quantified and visualized NEC‐induced changes to the gut vascular phenotype. Results: In vivo imaging required 60–100 s per animal. Relative to the healthy gut, NEC intestines showed a significant overall decrease (i.e. 64–72%) in perfusion, accompanied by vasoconstriction (i.e. 9–12%) and a reduction in perfusion entropy (19%)within sections of the vascular bed. Conclusions: Multicontrast imaging coupled with IVU‐based in vivo vascular phenotyping is a powerful new tool for elucidating NEC pathogenesis.